Differences in lower extremity kinematics and kinetics during a side-cutting task in patients with and without chronic ankle instability - Yue Xu; Yue Xu; Yizhang Mo; Yizhang Mo; Chengxiao Liu; Chengxiao Liu; Haofan Chen; Haofan Chen; Jianhao Zhao; Jianhao Zhao; Wanxia Zhang; Yang Yu; et al. (Frontiers in Sports and Active Living)
BackgroundPatients with chronic ankle instability (CAI) have demonstrated altered hip and knee movement strategies during walking and running, but these movement modalities do not involve changes in speed and direction, making it difficult to simulate the conditions of real sports, whereas side-cutting task can provide CAI patients with a more realistic athletic challenge. However, there is limited literature examining the kinematic and kinetic differences in the hip, knee, and ankle joints of CAI patients during the side-cutting task.ObjectiveTo assess differences in lower extremity joint kinematics and kinetics during the side-cutting task in individuals with and without CAI.DesignCross-sectional study.Participants48 males, 24 in each of the CAI group and healthy control group; 40 females, 20 in each of the CAI group and healthy control group.MethodsLower extremity three-dimensional kinematic and kinetics data were evaluated by using a three-dimensional motion analysis system during the initial contact (IC) and toe off (TO) while side-cutting.ResultsCompared with healthy controls, male patients with CAI exhibited greater hip flexion and external rotation angles, knee internal rotation angles, smaller knee flexion angles and ankle inversion angles, greater hip external rotation moments, and greater knee abduction moments; female patients with CAI exhibited smaller hip and knee flexion angles, greater hip external rotation angles, larger ankle inversion angles and internal rotation angles, smaller hip external rotation moments, and greater knee abduction moments.ConclusionOur findings indicate that patients with CAI exhibit altered lower limb joint kinematics and kinetics during side-cutting task, with significant sex-specific differences. These movement pattern changes involve proximal joint compensation to stabilize the unstable distal ankle joint; however, these compensatory changes are not always favorable. The greater hip external rotation moment and greater knee internal rotation angle demonstrated by male CAI patients, the smaller hip flexion angle and greater ankle internal rotation angle demonstrated by female CAI patients, and the smaller knee flexion angle and greater knee abduction moment common to both sexes may impair the lower limb's ability to effectively absorb and dissipate ground reaction forces, potentially elevating the risk of lower extremity injuries.